Przykłady „dobrej śmierci" u Aelreda z Rievaulx - Groń, Ryszard (Vox Patrum, 2005)
Inquiring into the historical works of Aelred of Rievaulx one can find a description of the exemplary ’good’ death of kings and other important persons. At the same time, they show that these descriptions deal with the phenomenon which would, in the XV century, later be called ars moriendi.